Elite soccer players` weekly workload assessment through a new training load and performance score - Pillitteri, G.; Rossi, A.; Bongiovanni, T.; Puleo, G.; Petrucci, M.; Iaia, F. M.; Sarmento, H.; Clemente, F. M.; Battaglia, G. (Research Quarterly for Exercise and Sport, 2024)
Purpose Monitoring players` training load allows practitioners to enhance physical performance while reducing injury risk. The aim of this study was to identify the key external load indicators in professional U19 soccer.